Strategies for Treatment of Dystonia - Chana-Cuevas, P (Springer-Verlag Wien, 2016)
Treatment of dystonias is generally symptomatic. To produce sufficient therapy effects, therefore, frequently a multimodal and interdisciplinary therapeutic approach becomes necessary, combining botulinum toxin therapy, deep brain stimulation, oral antidystonic drugs, adjuvant drugs and rehabilitation therapy including physiotherapy, occupational therapy, re-training, speech therapy, psychotherapy and sociotherapy. This review presents the recommendations of the IAB—Interdisciplinary Working Group for Movement Disorders Special Task Force on Interdisciplinary Treatment of Dystonia. It reviews the different therapeutic modalities and outlines a strategy to adapt them to the dystonia localisation and severity of the individual patient. Hints to emerging and future therapies will be given. © 2015, Springer-Verlag Wien.